Invasive Lobular Carcinoma With Extracellular Mucin: Not All Mucinous Mammary Carcinomas Are Ductal!. (February 2019) - Singh, Kamaljeet; DiazGomez, Berlly; Wang, Yihong; Ou, Joyce; Hansen, Katrine
Mucinous component in mammary carcinoma indicates ductal phenotype. Although intracytoplasmic mucin and signet ring cell change are frequently described with lobular carcinomas, extracellular mucin is not associated with lobular phenotype. We report 4 cases of invasive lobular carcinoma with extracellular mucin (ILCEM) and review findings of previously published cases of this rare ILC variant. Variable amount of extracellular mucin and pseudoglandular architectural pattern may lead to diagnosis of ILCEM as ductal mucinous carcinoma. Pathologists should be aware of this rare variant of ILC that will help identify more cases of this entity and clarify relevance of extracellular mucin production in ILC.